PERAN UN WOMEN TERHADAP DINAMIKA ESKALASI FEMICIDE DI NORTHERN TRIANGLE OF CENTRAL AMERICA - Joana, Rira; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Gender-based violence that victimizes women occurs all over the world. Cases of gender inequality in the Northern Triangle of Central America (NTCA) are more concerning because of discrimination and even femicide. Given the severity of the cases that occur, it is necessary to research the role of UN Women in overcoming cases of femicide both emotionally, character, and physically. The research method used in this research is qualitative with data collection techniques through document analysis and femicide graph data through ECLAC, the Gender Equality Observatory for Latin America and the Caribbean which explains femicide cases that occur in the NTCA region. This research uses international organization theory to explain how UN Women's role in the dynamics of femicide escalation in NTCA and the concept of gender-based violence to explain how violence has occurred in the region. The results of this study show that the role of UN Women is still insignificant to femicide cases. UN Women took steps through several campaigns to sensitize the local community, provide guidance through various programs to realize better gender equality, invite local governments to form legislation to ensnare perpetrators of violence. As well as, empowering women through providing opportunities for women in various sectors such as education, economy, social and politics. Keywords: Gender-Based Violence, UN Women, Femicide, NTCA, Law